The Average Radial Speed of Light From Near to Far Space Surrounding the Kerr–Newman Super-Gravitational Source - Pei, Ting-Hang (Frontiers in Astronomy and Space Sciences, 2022)
The Kerr-Newman metric is used to discuss the average radial speed of light from near to far space surrounding the super-gravitational source like a black hole which can be observed by a weak-gravitation reference frame such as an observer on the Earth. The velocity equation of light near the black hole is represented in the Boyer-Lindquist coordinates (t, r, θ, ϕ) and the main parameters are the Schwarzschild radius RS, the rotation term a, and the charged term RQ. From the calculations, the average radial speed of light from r=RS to r= αRS with α>1 is possibly observed exceeding c by an observer on the Earth. The result can extend to the large r place when the rotation of the black hole is high or the charge is very large. This average radial speed finally approaches to c far away from the black hole. We also propose a new explanation based on our results that the observation of the faster-than-light particle is due to the light bending near the Kerr-Newman black hole or supermassive star with very strong gravity. In addition, two superluminal theories used to explain the speed of light in astronomy are compared. One is the Doppler effect in special relativity, and the other is the change in the photon speed due to the QED contribution of one-loop vacuum polarization to the photon effective action. The former seems to mainly appear the change of the observed wavelength or frequency, while the latter is the probably random and irregular occurrences. Our explanation is based on the Kerr-Newman metric in General Relativity, and it extends the discussion from the flat spacetime in special relativity to the curved spacetime which is suitable for many superluminal observations near the super-gravitational sources like the black hole. Our calculations are used to verify the tangible observation like the M87 jet.